NASUP Emerging PDS Leader Award - Christopher Kennedy; Elleana Roseburgh (PDS Partners)
Purpose – This article highlights the most recent winner of NASUP’s Emerging PDS Leader Award. This award is annually awarded to teacher candidates who have shown leadership skills during their PDS partnership experiences. Design/methodology/approach – The article is written in an informative, narrative style. Findings – Due to the nature of this piece, there are no research findings. However, the article features the work of the NASUP’s Emerging Leader Award winner for 2024, Elleana Roseburgh from Baylor University. Elleana discusses the value of her PDS clinical experience on her development of her relationship-building and collaboration skills. Skills that have contributed to her leadership. Originality/value – This article draws additional attention to this exemplary partnership work and may inspire future nominations for potential emerging leaders.